Bilateral Tibial Stress Fractures and Osteoporosis in a Young Patient - Gurbuz, Ali; Gur, Mustafa (Sage Publications Inc, 2022)
Stress fractures result from microscopic bone injury due to repetitive submaximal stress and include fatigue and insufficiency fracture components. Fatigue fractures generally occur in runners and athletes and are caused by abnormal physical load on the bone. On the other hand, insufficiency fractures are generally seen in the elderly secondary to osteoporosis, typically involving the pelvis and surrounding bones. Insufficiency fracture occurs as a result of normal loading in the abnormal bone. In this case report, we describe a young patient with bilateral tibial stress fractures with both fatigue and insufficiency components.
Keywords: stress fracture; tibia; osteoporosis